Biomarker Changes after Strenuous Exercise Can Mimic Pulmonary Embolism and Cardiac Injury—A Metaanalysis of 45 Studies. (6th January 2020) - Sedaghat-Hamedani, Farbod; Kayvanpour, Elham; Frankenstein, Lutz; Mereles, Derliz; Amr, Ali; Buss, Sebastian; Keller, Andreas; Giannitsis, Evangelos; Jensen, Katrin; Katus, Hugo A; Meder, Benjamin
Abstract: BACKGROUND: Biomarkers are well established for diagnosis of myocardial infarction [cardiac troponins, high-sensitivity cardiac troponins (hs-cTn)], exclusion of acute and chronic heart failure [B-type natriuretic peptide (BNP), N-terminal proBNP (NT-proBNP)] and venous thromboembolism (d -dimers). Several studies have demonstrated acute increases in cardiac biomarkers and altered cardiac function after strenuous sports that can pretend a cardiovascular emergency and interfere with state-of-the-art clinical assessment. METHODS: We performed a systematic review and metaanalysis of biomarker and cardiovascular imaging changes after endurance exercise. We searched for observational studies published in the English language from 1997 to 2014 that assessed these biomarkers or cardiac function and morphology directly after endurance exercise. Of 1787 identified abstracts, 45 studies were included. RESULTS: Across all studies cardiac troponin T (cTnT) exceeded the cutoff value (0.01 ng/mL) in 51% (95% CI, 37%–64%) of participants. The measured pooled changes from baseline for high-sensitivity cTnT (hs-cTnT) were +26 ng/L (95% CI, 5.2–46.0), for cTnI +40 ng/L (95% CI, 21.4; 58.0), for BNP +10 ng/L (95% CI, 4.3; 16.6), for NT-proBNP +67 ng/L (95% CI, 49.9; 84.7), and for d -dimer +262 ng/mL (95% CI, 165.9; 358.7). Right ventricular end diastolic diameter increased and right ventricular ejection fraction as well as the ratio of the early to late transmitral flow velocities decreased after exercise, while no significant changes were observed in left ventricular ejection fraction. CONCLUSIONS: Current cardiovascular biomarkers (cTnT, hs-cTnT, BNP, NT-proBNP, and d -dimer) that are used in clinical diagnosis of pulmonary embolism, acute coronary syndrome, and heart failure are prone to alterations due to strenuous exercise. Hence, it is necessary to take previous physical exercise into account when a cardiac emergency is suspected.